Prediction of the potential distribution area of Glycyrrhiza inflata in China using a MaxEnt model - Du, Zhen-zhu; Xu, Wen-bin; Wang, Yu-xia; Yan, Ping; Ma, Zhan-cang; Huang, Gang; Li, Hong-bin (Frontiers in Ecology and Evolution, 2024)
Glycyrrhiza inflata Batalin is an important medical plant of the genus Glycyrrhiza. It is one of the key protected plants in China, distributing in the desert areas of southern Xinjiang and Dunhuang of Gansu Province. It has a strong resistance to drought, heat, and salt stresses, and plays a pivotal role in sand fixtion in desert areas. In this study, based on 157 valid distribution records and eight environmental factors including climate factors and altitude, the potential distribution area of G. inflata in the last glacial maximum, middle Holocen, modern and future (2050) times in China were predicted, using the optimized MaxEnt model and ArcGis 10.2 software. The results showed that the predicted distribution area was highly consistent with the current distribution range, and the area under the receiver operating characteristic (AUC) curve was 0.986, indicating that the prediction performance was excellent. The key climatic factors affecting the distribution were precipitation in December and the average annual precipitation. Meanwhile, the suitable area of G. inflata in modern times was 1,831,026 km2, mainly distributed in Turpan-Hami Basin, Tarim Basin, and Dunhuang of Gansu Province, with Lop Nur Town of Xinjiang as the distribution center. In 2050, the potential suitable area of G. inflata in China will be 1,808,090 km2, of which the area of highly suitable area will be 250,970 km2, which is 150,600 km2 smaller than that in modern times, with a reduction rate of 60.0%. Therefore, there is a trend of great reduction in the suitable area of G. inflata.From the last glaciation maximum to the middle Holocene, the geographical distribution center shifted to the southwest margin of the Kumtag Desert, Xinjiang, then later continued to shift to the southwest. This study will provide a basis for understanding the origin and evolution of G. inflata, developing conservation strategies to minimize the impacts of environment change, and utilizing plant resource.